Effect of Delay in Tuberculosis Diagnosis on Pre-Diagnosis Cost - Aldhubhani, Adel Hamood Noman; Ibrahim, Mohamed Izham Mohamed; Ibrahim, Pazilah; S. Anaam, Mohamed; Alshakka, Mohamed (Journal of Pharmacy Practice and Community Medicine)
Background: Delay in TB diagnosis can increase the financial burden of patients, especially those who are suffering from poverty. The cost of Tuberculosis (TB) diagnosis, either pre- or post diagnosis, is an important concern in TB control programs worldwide. The new Tuberculosis (TB) patients that diagnosed at Tuberculosis referral centre, Sana’a, Yemen were the subjects of this study. Objective: This study aimed to evaluate the pre-diagnosis costs for delayed TB patients (prior to the actual TB diagnosis) in a tuberculosis referral center in Sana’a, Yemen. Materials and Methods: A cross-sectional study on newly diagnosed TB patients was performed by the National Tuberculosis Control Program in a tuberculosis center in Sana’a, Yemen. A total of 505 new TB patients were interviewed using a questionnaire. The study period was from 2008 to 2010. Information on the pre-diagnosis costs (direct medical and non-medical costs) for the newly diagnosed TB patients was collected. Results: Differences in the pre-diagnosis costs between delayed (%) and non-delayed patients (%) were obtained. The medical (medication, laboratory investigation, and chest X-ray test) and non-medical (food, transportation, and accommodation) costs incurred by the TB patients were statistically different between the delayed and non-delayed TB groups (p < 0.05). Conclusion: The delayed group incurred extra costs prior to the actual TB diagnosis compared with the non-delayed group. Promoting information and awareness on TB and health care systems in both public and private sectors should be done for both groups to detect TB at an earlier stage and to reduce extra costs incurred during the pre-diagnosis period.
Keywords: Cost; TB; DOTS; Yemen; Prediagnosiss; Delay